A Simple Macrofiscal Model for Policy Analysis : An Application to Morocco - Baksa, Daniel (IMF Working Papers; Working Paper ;, 2021)
The paper describes a semistructural macrofiscal approach to simulating and forecasting macroeconomic policies. The model focuses on only a few variables that are consistent with the New Keynesian framework. Thanks to its simplicity, it facilitates an initial and intuitive understanding of monetary and fiscal policy transmission channels, and their main impact on economic activity. The model is adapted to Morocco and we demonstrate its application with an illustrative scenario of policy responses to a slower-than-expected recovery from the Covid-19 pandemic, under different monetary policy and exchange rate regimes.